2020
DOI: 10.3390/membranes10110335
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Multilayer Hybrid Coating on PSF Hollow Fiber Membrane for Enhanced Gas Separation

Abstract: One of the most critical issues encountered by polymeric membranes for the gas separation process is the trade-off effect between gas permeability and selectivity. The aim of this work is to develop a simple yet effective coating technique to modify the surface properties of commonly used polysulfone (PSF) hollow fiber membranes to address the trade-off effect for CO2/CH4 and O2/N2 separation. In this study, multilayer coated PSF hollow fibers were fabricated by incorporating a graphene oxide (GO) nanosheet in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 53 publications
(61 reference statements)
1
10
0
Order By: Relevance
“…The performance of the prepared Pebax ® 2533-UiO-66-NH 2 /PP thin film mixed matrix hollow fiber membranes were compared with Pebax ® -based mixed matrix membranes containing various types of fillers ( Table 1 ). The gas separation performance of Pebax ® 2533-UiO-66-NH 2 /PP thin film mixed matrix hollow fiber membrane containing 10 wt% UiO-66-NH 2 is comparable with previous reported Pebax ® -based mixed matrix membranes containing various types of fillers in literature [ 14 , 33 , 40 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. The prepared membrane shows a high CO 2 /N 2 ideal selectivity equal to 37 with a CO 2 permeance 25.81 GPU at feed pressure 2 bar.…”
Section: Resultssupporting
confidence: 87%
“…The performance of the prepared Pebax ® 2533-UiO-66-NH 2 /PP thin film mixed matrix hollow fiber membranes were compared with Pebax ® -based mixed matrix membranes containing various types of fillers ( Table 1 ). The gas separation performance of Pebax ® 2533-UiO-66-NH 2 /PP thin film mixed matrix hollow fiber membrane containing 10 wt% UiO-66-NH 2 is comparable with previous reported Pebax ® -based mixed matrix membranes containing various types of fillers in literature [ 14 , 33 , 40 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. The prepared membrane shows a high CO 2 /N 2 ideal selectivity equal to 37 with a CO 2 permeance 25.81 GPU at feed pressure 2 bar.…”
Section: Resultssupporting
confidence: 87%
“…The 2019 review contains studies on the influence of the nature and composition of the internal coagulant, its temperature, and the contact time of the casting polymer solution with it [10]. The latest review of 2020 contains research on the development of casting methods of HF membranes that are safe for humans and the environment [11] Polysulfone (PSf) is one of the most common polymers for the manufacture of HF membranes for micro-, ultrafiltration, gas separation, and membrane contactors [12][13][14]. In scientific works on the formation of HF membranes from this polymer, the influence of the molecular weight and concentration of the matrix polymer, the solvent used, the type of pore-forming agent, its molecular weight and concentration, the nature and composition of the coagulant on their transport and separation properties has been studied in detail [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…To improve the separation performance of membranes, it has been suggested that different organic or inorganic materials, such as fluorescent material (TPE) [ 8 ], metal nanoparticles [ 9 ], graphene oxide (GO) [ 10 ], carbon nanotubes (CNTs) [ 11 ], metal–organic frameworks (MOFs) [ 12 ], TiO 2 [ 13 , 14 ] and silica [ 15 , 16 ] are incorporated. Compared with other materials, silica is a common and low-cost functional filler for organic–inorganic hybrid membranes.…”
Section: Introductionmentioning
confidence: 99%